Law and compassion: between ethics and economy, philosophical speculation and arche-ology. Issue 2 (12th May 2017) - Diamantides, Marinos
Abstract: This paper examines the relationship between law and compassion from the perspective of two diverse scholars. For philosopher Emmanuel Levinas, rejecting the idea homo homini lupus, there can simply be no organised society but for a primordial, unauthorised, human vocation for compassion (egoism and violence, for him, are nothing but attempts to repress this). Levinas, however, must be understood, as speaking of compassion not in the usual sense, that is as involving a human capacity for, and cultures of, empathy; he defines it, rather, in phenomenological terms, as an irreducible excess of affectivity for the ultimately meaningless suffering of another, beyond all theodicy and causality, whom one is ethically commanded to offer succour to as if s/he is a 'higher' and absolutely unique Other, prior to any comparison and judgment. General legal principles and rigorous rules, Natural Justice and positive law are equally 'born' of such an-archic, individuated, compassion for which one can only retroactively account. Justice is 'born' as one attempts to justify to third parties why one's care benefits some but not others; the paper argues that this perspective is preferable to prioritising empathic compassion over law for it binds compassion with responsibility. Turning to Giorgio Agamben, the role of compassion takes on a darker character; his historicised investigations of the 'Western-Christian' paradigm shows how the Greek and Roman legal principles of epieikeia and aequitas merged with the Christian postulates of God-dictated philanthropy and 'divine economy' (Gr: oikonomia ), leading to – instead of ethical anarchy followed by with infinite responsibility (Levinas) – anomie, legal exceptionalism and social control via patronage and other biopolitical practices to spectacles of compassion. This suggests that what Levinas calls 'ethical anarchy' has been captured by economic rationality and endless processes of anomic management that are equally free of ethical constraints as they are from legal and political decision. With reference to contemporary examples from the 'law and emotion' debates, medical laws and humanitarianism, the paper asks the reader to ponder upon the importance, if any, of Levinas's thesis in a world where the expediency of managerial rationality, the secular heir of divine oikonomia, prevails over moral, legal and political principle.